Enhancing Shear Strength in RC Beams: A Synergistic Approach with Steel Chips and Wire Mesh - Hasnain Kazam; Syed Saqib Mehboob; Matiullah (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study explores a hybrid approach aimed at enhancing the shear performance of reinforced concrete (RC) beams. The methodology involves the incorporation of industrial steel chips having length 75mm to 100mm in combination with varying widths of wire mesh reinforcement. Comprehensive shear tests were conducted on precisely prepared beam specimens measuring 150mm×150mm×900mm to assess shear strength, crack patterns, and failure modes. The study induces steel chips into the concrete mix at a rate of 0.9% by weight and comprises eight sets of specimens, including a control sample without any mesh reinforcement, along-with specimens reinforced with wire mesh strips ranging from 12.5mm to 87.5mm in width. Notably, the inclusion of steel chips and wire mesh enhances the shear behavior of concrete beams across all samples. As the steel chips and wire mesh acts like small-diameter bars, contributing to the enhancement of shear by improving the interlocking of concrete constituents and eff ectively distributing stresses throughout the beam’s cross-section, leading to distinctive diagonal crack patterns on the beam surfaces. The study unveils that with the increasing width of the wire mesh, there is an increase in the number of cracks while the crack widths decreases. The test outcome reveals that percentages increase of 13.66, 22.89, 31.37, 46.50, 55.00, 66.80 and 78.60 respectively, demonstrating the eff ective enhancement of shear strength through the utilization of wire mesh and steel chips.